A New Adsorption Isotherm for Heterogeneous Sorbents - V.P. Shkilev; V.V. Brei (Adsorption Science & Technology)
An adsorption isotherm has been suggested for the intended description of the experimental isotherms for the adsorption of gases and vapours on heterogeneous surfaces. Two parameters of the suggested equation, which characterize the heterogeneity of a sorbent, were expressed in the form of explicit functions of temperature as well as of variance and the excess coefficient for the corresponding energy distribution of adsorption sites. The presence of such explicit expressions allowed the application of the suggested equation for the description of the dependence of the adsorption not only on pressure but also on temperature. The adsorption of N 2 on TiO 2 was considered as an example. It was shown that the suggested equation could be used as the thermal equation of state for a real adsorption system over quite wide ranges of temperature and pressure.